PERANCANGAN SISTEM PEMBAYARAN PELAYANAN PADA GEREJA BETHEL INDONESIA SOKARAJA KIDUL BERBASIS WEBSITE - Sugianto, Dyana Natalia; Manurung, Ria; Racmar, Dhany Faizal Racma3 Faizal (Electro Luceat, 2024)
The purpose of this system is to simplify church payments and management, reduce human error, and improve the efficiency of the payment process. Planning, analysis, design, coding, implementation, and evaluation are all stages in the Life Cycle of System (SDLC) model used in this system development methodology. Visual Studio Code, phpMy Admin, and MySQL were used to build this system. Several real-time reports are generated by this system, including the total receipts report, expenditure report, tithe report, payment report by name, month, and year, and payment slip report. During the development process of this system, several users could manage the system and assess how it worked according to its users' needs. The system has security features to ensure that only authorized users can access transaction information. In addition, automated and organized payment management makes it easier to manage the church's finances regularly. This web-based system helps digitalize church administration and increase congregants' trust in more transparent fund management. Churches can implement this system to speed up decision-making and financial management.